Evaluation of Adoption of Interlocking Soil Technology in Development of Adequate and Sustainable Housing Projects in Nandi County, Kenya. - Euginia, Chang’ach; Omboto, Prof. Peter; Mulongo, Prof. Leonard (International Journal of Scientific Research and Management (IJSRM), 2019)
Project success incorporates both project management success and product success. The basic criteria for evaluating project success are scope, time, cost, and client satisfaction with the final product or service.  The use of interlocking stabilized soil block technology in housing projects has been promoted in Kenya as a means to address poverty, sustainable housing and housing affordability challenges facing many Kenyans. The programme was conceptualized, planned and implemented across the country. The uptake of the technology has however been slow. This study sought to evaluate the adoption of the interlocking soil technology in development of adequate and sustainable housing projects in Nandi County. The variables analyzed for this study were; understanding of the processes of production, community participation, benefits of the technology and the challenges of cost and information dissemination. The study was guided by the Innovation Diffusion and Systems theories. The study adopted a descriptive survey design. 155 households were sampled out of the 81,672 households in the target population. Quantitative data was collected using questionnaires. Data was analyzed using descriptive and inferential statistics. The study established that the interlocking technology is not widely practiced. There is an average understanding of the processes of production, community participation is not widely embraced, information dissemination is not effective and efficient and the costs were not affordable. The study recommends that action should be taken to promote better understanding of the processes of production, enhance community participation and addressing the challenges of cost and information dissemination.